1883 Wis. Sess. Laws 370, ch. 152, ch. 6 [sic], § 8, pt. 17. - (:unkn) unknown (My University, 1883)
To prohibit, restrain or regulate the discharge of fire-arms and the explosion of gunpowder and guncotton, and the firing of firecrackers and fireworks of any kind within the city.
Keywords: DISCHARGE